An Analytical Study of the Foreign Direct Investment Attractiveness Gap in Arab States - BOUTEKOUK, Amar; DEHANE, Mohammed; ACHOURI , Naim (Journal of Human Sciences, 2025)
This study aims to diagnose and analyze the reality of the foreign direct investment (FDI) attractiveness gap in Arab countries, identifying the most influential factors in order to enhance their competitive position in attracting foreign investment. To achieve this, the paper seeks to establish specific metrics for measuring this gap in Arab countries. This is done by relying on the descriptive approach and examining the economic conditions of Arab countries during the period spanning from 2013 to 2023. The study concludes by proposing a set of metrics to measure FDI attractiveness, such as the quota criterion, the average global ranking index for the business climate, and the composite guarantee index. By analyzing the results of various measurements of the FDI attractiveness gap in Arab countries, the study reveals significant disparities among Arab countries in attracting FDI, as well as a decline in its volume. It attributes the reasons for the reduced flow of FDI to Arab countries and the emergence of this gap to a number of factors, the most important of which are: the slow pace and limited scope of economic reform programs, bureaucracy, weak government oversight in enforcing laws, and the capacity of Arab countries to absorb foreign direct investment, among others.